2006
DOI: 10.1271/bbb.60216
|View full text |Cite
|
Sign up to set email alerts
|

Sake Yeast Suppresses Acute Alcohol-Induced Liver Injury in Mice

Abstract: Brewer's and baker's yeasts appear to have components that protect from liver injury. Whether sake yeast, Saccharomyces cerevisiae Kyokai no. 9, also has a hepatoprotective effect has not been examined. Here we show that sake yeast suppresses acute alcoholic liver injury in mice. Male C57BL/6 mice that had been fed a diet containing 1% sake yeast for two weeks received three doses of ethanol (5 g/kg BW). In the mice fed sake yeast, ethanol-induced increases in triglyceride (TG) and glutamate pyruvate transamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…The concentrations of serum total lipid, triglyceride, total-cholesterol and HDL-cholesterol showed a significant decrease by SEP supplementation in alcohol feeding rats. Many reports indicate that alcohol intake significantly increases the levels of serum triglyceride and cholesterol [11,23], but this is not in agreement with the results in the present study. The current study demonstrated a possibility that SEP would be able to decrease the serum lipid concentrations by the simultaneous addition of alcohol.…”
Section: Effect Of Sep On Serum Lipid Concentrationscontrasting
confidence: 99%
“…The concentrations of serum total lipid, triglyceride, total-cholesterol and HDL-cholesterol showed a significant decrease by SEP supplementation in alcohol feeding rats. Many reports indicate that alcohol intake significantly increases the levels of serum triglyceride and cholesterol [11,23], but this is not in agreement with the results in the present study. The current study demonstrated a possibility that SEP would be able to decrease the serum lipid concentrations by the simultaneous addition of alcohol.…”
Section: Effect Of Sep On Serum Lipid Concentrationscontrasting
confidence: 99%
“…4B). We have shown in a previous report that the ingestion of a diet containing 1% sake yeast suppressed acute alcoholic liver injury; 13) the ethanol-induced increases in TG in the ethanol and 1% sake yeast/ethanol groups were 2.3-and 1.6-fold, respectively; 13) the ethanol-induced increases in ALT in the ethanol and 1% sake yeast/ethanol groups were 6.0-and 1.8-fold, respectively.…”
Section: )mentioning
confidence: 74%
“…We have demonstrated that a diet containing 1% sake yeast repressed both the ethanol-induced elevation of TG and ALT and the ethanol-induced reduction of the hepatic SAM level. 13) Even though a diet containing 0.25% sake yeast repressed the ethanol-induced reduction of hepatic SAM level (Fig. 5), sake yeast could not fully repress the ethanol-induced elevations of TG and ALT (Figs.…”
Section: )mentioning
confidence: 93%
See 2 more Smart Citations